2016
DOI: 10.4103/0974-9233.175886
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the posterior capsule rupture rates associated with conventional (start to finish) versus reverse methods of teaching phacoemulsification

Abstract: Purpose:Comparison of the rates of posterior capsule rupture (PCR) associated with conventional versus a reverse method of teaching phacoemulsification.Methods:Trainees were taught conventional (start-to-finish) phacoemulsification beginning with an incision (tunnel construction) to capsulorhexis, sculpting, nucleus cracking, segment removal, cortex aspiration, intraocular lens implantation, and viscoelastic removal. In the reverse method, after incision and capsulorhexis, the trainees were progressively taugh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…demonstrated that the conventional way of teaching cataract surgery is equally safe and effective. [ 21 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…demonstrated that the conventional way of teaching cataract surgery is equally safe and effective. [ 21 ]…”
Section: Discussionmentioning
confidence: 99%
“…The PCR rate in trainees performing cataract surgery is variable and ranges from 4.9% to 10%. [ 2 9 16 21 23 27 29 ] The variability in the occurrence of PCR in various studies is probably due to the differing trainee experience, methods followed to assess the teaching method and stage of intervention by the supervisor.…”
Section: Discussionmentioning
confidence: 99%
“…These studies only emphasize that various modalities have been tried to improve the resident surgical outcomes. [ 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…Because capsulorrhexis and lens nucleus cracking and chopping are among the initial steps of phacoemulsification cataract extraction surgery which have a steep learning curve, some attending physicians would prefer to teach phacoemulsification starting from reverse order: the trainee surgeon performs I/A and IOL insertion after the supervisor completes capsulorrhexis and phacoemulsification of the lens. 28 , 32 , 33 This reverse teaching approach could deprive the chances of novice surgeons to practice performing the tasks that have the steepest learning curves, but this approach is better for patient care and safety.…”
Section: Discussionmentioning
confidence: 99%